Trend 1990 - 2010. Energy Information Administration. International Energy Statistics: Natural Gas Production | Country: Faroe Islands | Indicator: Gross Natural Gas Production (Billion Cubic Feet), 1990-2010. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 004-014-011. - Energy Information Administration (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Energy Information Administration (2015). International Energy Statistics: Natural Gas Production | Country: Faroe Islands | Indicator: Gross Natural Gas Production (Billion Cubic Feet), 1990-2010. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 004-014-011. Dataset: Provides statistics on natural gas production by country, as available. Natural gas production refers to the volume of natural gas withdrawn from reservoirs less (1) the volume returned to such reservoirs in cycling, repressuring of oil reservoirs, and conservation operations; less (2) shrinkage resulting from the removal of lease condensate; and less (3) non-hydrocarbon gases where they occur in sufficient quantity to render the gas unmarketable. Volumes of gas withdrawn from gas storage reservoirs and native gas, which has been transferred to the storage category, are not considered production. Flared and vented gas is also considered production. (This differs from "Marketed Production" which excludes flared and vented gas.) To assure comparability of data across countries, natural gas production numbers exclude non-hydrocarbon gases for all countries. The dataset provides data for 220 countries, as available, on energy-related metrics, including total and crude oil production, oil consumption, natural gas production and consumption, coal production and consumption, electricity generation and consumption, primary energy, energy intensity, CO2 emissions and imports and exports for all fuels. Data are sourced from Energy Information Administration research, as well as from national and international agencies, listed at http://www.eia.gov/cfapps/ipdbproject/docs/sources.cfm. Category: Energy Resources and Industries, International Relations and Trade Source: Energy Information Administration The Energy Information Administration (EIA), created by Congress in 1977, is an independent statistical and analytical agency within the United States Department of Energy. Its mission is to provide policy-independent data, forecasts, and analyses to promote sound policy making, efficient markets, and public understanding regarding energy and its interaction with the economy and the environment. http://www.eia.doe.gov/ Subject: Natural Gas, Energy Production, Natural Gas Production